THE EFFORT TO INCREASE THE LEARNING RESPONSIBILITY OF MATHEMATICS USING RECIPROCAL TEACHING MODEL IN STUDENT CLASS X - Annisa Rafiqa Noor Abdillah; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Teacher-centered learning results in students being less responsible for learning. Therefore, there is a need for individual efforts to improve the student's learning responsibility. This study aims to improve the Responsibility of learning mathematics by using the Reciprocal Teaching model on the students of class X OA Semester Even Vocational High School (SMK) Yudha Karya Magelang academic year 2014/2015. This research is a research type of Classroom Action Research (CAR). Subjects in this study were students of class X OA, even semester SMK Yudha Karya Magelang academic year 2014/2015.In comparison, the object under study in this research is applying the Reciprocal Teaching model on the students of class X OA Semester Even SMK Yudha Karya Magelang academic year 2014/2015. The study was conducted two cycles from three planned cycles. Data were collected by observation method, questionnaire, repeat test. Data analysis used is descriptive qualitative. The results showed that the Reciprocal Teaching model on the students of class X OA Semester Even SMK Yudha Karya Magelang academic year 2014/2015 increase the Responsibility of learning. This is evident from the observation result of students' learning responsibility every cycle has increased: the percentage of success of students' learning in cycle I equal to 52,08% (Enough). In cycle II, this increased to 80,03% (Very Good). The percentage of students who completed each cycle also increased the cycle I obtained by 37.93%. The second cycle increased to 68.97% in the second cycle.